Ultrasonic Velocities in Intergranular Creep Damaged Copper and Oblate Ellipsoidal Void Model - Hirao, Masahiko; Fukuoka, Hidekazu; Morishita, Tomohiro (Transactions of the Japan Society of Mechanical Engineers Series A, 1995)
The dependence of the ultrasonic velocities on the creep damage can be used for its nondestructive evaluation. This study discussed the validity of the oblate ellipsoidal void model to predict their relationship. In the experiment, the ultrasonic velocities and the density change in creep damaged coppers were measured. The prediction by the spherical void model gives good agreement with the experimental results in the initial stage of the damage process. As the damage progresses, this model is no longer valid because of the anisotropy in ultrasonic velocities. The oblate ellipsoidal void model is thus used to explain the anisotropy. However, this model shows an opposite tendency in some cases of velocity rate changes with decrease in density. The density decrease estimated from the ultrasonic velocities is about two times larger than the direct measurement. Metallographical observations show that the clustering of voids on the grain boundaries and their orientation distribution should be considered.